Downregulation of a CYP74 Rubber Particle Protein Increases Natural Rubber Production in Parthenium argentatum - Placido, Dante F.; Dong, Niu; Dong, Chen; Cruz, Von Mark V.; Dierig, David A.; Cahoon, Rebecca E.; Kang, Byung-guk; Huynh, Trinh; Whalen, Maureen; Ponciano, Grisel; McMahan, Colleen (Frontiers in Plant Science, 2019)
We report functional genomics studies of a CYP74 rubber particle protein from Parthenium argentatum, commonly called guayule. Previously identified as an allene oxide synthase (AOS), this CYP74 constitutes the most abundant protein found in guayule rubber particles. Transgenic guayule lines with AOS gene expression down-regulated by RNAi (AOSi) exhibited strong phenotypes that included agricultural traits conducive to enhancing rubber yield. AOSi lines had higher leaf and stem biomass, thicker stembark tissues, increased stem branching and improved net photosynthetic rate. Importantly, the rubber content was significantly increased in AOSi lines compared to the wild-type (WT), vector control and AOS overexpressing (AOSoe) lines, when grown in controlled environments both in tissue-culture media and in greenhouse/growth chambers. Rubber particles from AOSi plants consistently had less AOS particle-associated protein, and lower activity (for conversion of 13-HPOT to allene oxide). Yet plants with downregulated AOS showed higher rubber transferase enzyme activity. The increase in biomass in AOSi lines was associated with not only increases in the rate of photosynthesis non-photochemical quenching (NPQ), in the cold, but also in the content of the phytohormone SA, along with a decrease in JA, GAs, and ABA. The increase in biosynthetic activity and rubber content could further result from the negative regulation of AOS expression by high levels of salicylic acid in AOSi lines and when introduced exogenously. It is apparent that AOS in guayule plays a pivotal role in rubber production and plant growth.